2008
DOI: 10.1177/070674370805301104
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care for People with Severe Persistent Mental Illness: A Review of the Literature

Abstract: A systematic overview of the literature on palliative care for people with severe persistent mental illness (SPMI) was conducted to inform clinical practice, research, and education. Empirical studies and nonempirical papers were included. Few empirical studies exist. There is even less information about the palliative care needs of, or the nature of palliative care provided to, people with SPMI. Mental health, primary care, and palliative care providers need to partner with people who have SPMI in developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
136
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(141 citation statements)
references
References 55 publications
(132 reference statements)
1
136
1
3
Order By: Relevance
“…Symptoms and behaviours exhibited by a person with SPMI can affect assessment and interpretation of physical symptoms by clinicians, the care that is given, and access to certain care environments, including hospice (McCasland ; Reeves & Torres ; Woods et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Symptoms and behaviours exhibited by a person with SPMI can affect assessment and interpretation of physical symptoms by clinicians, the care that is given, and access to certain care environments, including hospice (McCasland ; Reeves & Torres ; Woods et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…2005a; Rentmeester ; Woods et al . ). Studies have identified that people with SPMI have the capacity to make decisions about end‐of‐life care and participate in advance care planning when their symptoms are in remission (Baker ; Foti et al .…”
Section: Introductionmentioning
confidence: 97%
“…The requirement stems from Cicely Saunders' notion that addressing “Total Pain” demands a team of specialists practicing interprofessionally to provide comprehensive, whole-person care. Ogawa et al (2010) examined 2000 consecutive palliative care referrals in a single cancer hospital in Japan and determined that psychiatrists (as members of the palliative care team) were involved in the care of 80% of all referrals, with delirium, adjustment disorder, depression, and dementia among the most common issues of focus for the psychiatric specialists [43]. In a further study, the same authors surveyed consult-liaison psychiatrists at 375 government-designated cancer hospitals in Japan.…”
Section: Recent Advances In Palliative Care Psychiatrymentioning
confidence: 99%
“…In other words, the main thrust of psychiatric palliative care to date has been to bring psychiatric expertise to seriously-ill patients, many of whom had not previously experienced mental illness. Conversely, there has been little attention to developing models for the application of palliative care principles to the care of patients with chronic mental illness, with some important exceptions [4345]. Secondly, palliative care practice entails a number of important ethical concerns, some of which bear uniquely on issues relevant to mental health.…”
Section: Steps Aheadmentioning
confidence: 99%
“…7 Ms. Lee, like so many patients, was suffering because of system failures. Many of the challenges facing the hospital were not unique: significant psychiatric issues, prolonged nonadherence to medical advice, and end-of-life decisionmaking combine to create an ethically dense and vexing situation in any hospital.…”
mentioning
confidence: 99%